2013
DOI: 10.1590/s0101-20612013005000029
|View full text |Cite
|
Sign up to set email alerts
|

Sesame and flaxseed oil: nutritional quality and effects on serum lipids and glucose in rats

Abstract: This study evaluated the nutritional value of sesame and flaxseed oils and their effects on the lipid and glucose profile of rats fed diets containing different fat combinations. Fatty acid composition, refractive index, and iodine and saponification values were analyzed to characterize the oils. In the biological assay, Wistar rats were fed different diets, whose fat composition consisted of varying combinations of flaxseed oil, sesame oil, and animal fat. The primary constituents of the sesame oil were oleic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 42 publications
(23 reference statements)
4
36
2
3
Order By: Relevance
“…The ratio of ω 6 : ω 3 fatty acids is important because it presents potential health benefits (Guimarães et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The ratio of ω 6 : ω 3 fatty acids is important because it presents potential health benefits (Guimarães et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…In this study, the PUFA level in the oil was 86.72% and the percentage of saturated fatty acids (SFA) was 7.86%. According to Guimarães et al (2013), recent studies have demonstrated increased interest in PUFA as essential components of the human diet because they play an important role in various biological systems. The reported PUFA : SFA ratio was >11 in the extract obtained in this work.…”
Section: X X X X Xmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence report that dyslipidemia associated with HAART accelerates the development of atherosclerosis and has a higher incidence of cardiovascular events, which is possibly related to the duration of the treatment [32,33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…The sesame oil increases gamma-tocopherol of plasma and boosts Vitamin E activity, which prevents cancer and heart disease. In addition, it contains sesamolin and sesamol, which have antioxidant activity (Guimarães et al, 2013;Protonotariou, Evageliou, Yanniotis, & Mandala, 2013).…”
Section: Introductionmentioning
confidence: 99%